2020
DOI: 10.1109/lwc.2020.3017169
|View full text |Cite
|
Sign up to set email alerts
|

The α-η-κ-F Composite Fading Distribution

Abstract: In this paper, we propose the α-Lomax distribution as a new compound fading channel model. This new distribution generalizes the recently introduced Lomax fading channel model. It is worth noting that the Lomax distribution is a decreasing function, while the α-Lomax is a unimodal function, offering greater flexibility in modeling wireless fading channels. In particular, we derive closed-form expressions for the probability density function and cumulative distribution function for the instantaneous signal-to-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…and q l are the mean values of the in-phase and quadrature phase components of the multipath cluster l. From (11), one can note that the PDF of R can be derived by averaging the PDF of the α − κ − µ fading over the PDF of ϑ and ξ RVs. However, the PDF of the α − κ − µ fading is included the modified Bessel function of the first kind, I υ (.)…”
Section: Statistical Properties Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…and q l are the mean values of the in-phase and quadrature phase components of the multipath cluster l. From (11), one can note that the PDF of R can be derived by averaging the PDF of the α − κ − µ fading over the PDF of ϑ and ξ RVs. However, the PDF of the α − κ − µ fading is included the modified Bessel function of the first kind, I υ (.)…”
Section: Statistical Properties Ofmentioning
confidence: 99%
“…conditions were derived in [10]. These models were then unified in a single distribution which is named α − η − κ − F composite fading [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the wireless fading channels can be described by a significant number of general models, which are gaining in importance more and more. eir flexibility makes them suitable for situations in which none of the traditional distributions give a good fit [14][15][16][17][18][19][20][21][22][23][24][25]. In addition, their convenience is recognized in practical and realistic environments.…”
Section: Introductionmentioning
confidence: 99%
“…The composite α-F fading channel was investigated in [8] with applications to the outage probability (OP) and average bit error rate (ABER) of the wireless communications systems. The composite α-κ-F and α-η-F fading distributions were analysed in [9] whereas the authors in [10] suggested the αη-κ-F fading model.…”
Section: Introductionmentioning
confidence: 99%